1981
DOI: 10.1084/jem.153.3.677
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specific T cell clones restricted to unique F(1) major histocompatibility complex determinants. Inhibition of proliferation with a monoclonal anti-Ia antibody

Abstract: The existence of T cells specific for soluble antigens in association with unique F(1) or recombinant major histocompatibility complex (MHC) gene products was first postulated from studies on the proliferative response of whole T cell populations to the antigen poly(Glu(55)Lys(36)Phe(9))(n) (GLφ). In this paper we use the newly developed technology of T lymphocyte cloning to establish unequivocally the existence of such cells specific for GLφ and to generalize their existence by showing that F(1)- specific cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 47 publications
(56 reference statements)
2
3
0
Order By: Relevance
“…Early studies of class 11-associated immune response genes in mice revealed the phenomenon of Zr gene complementation, in which an F1 hybrid between two low or nonresponder mouse strains for a particular antigen was found to be a high responder (Stimpfling & Durham, 1972;Dorf et al, 1975). A number of the experimental cases of this were eventually found to be explained by the phenotypic 'rescue' of I-E chains from En mouse strains by association with complementing chains from the second parent of the F, (Sredni et al, 1981). It is interesting to recall, in the light of the present findings, that one of the cases of Zr gene complementation in the rat, described by Giinther and Rude (1975), involved RTld.…”
Section: Discussionsupporting
confidence: 60%
“…Early studies of class 11-associated immune response genes in mice revealed the phenomenon of Zr gene complementation, in which an F1 hybrid between two low or nonresponder mouse strains for a particular antigen was found to be a high responder (Stimpfling & Durham, 1972;Dorf et al, 1975). A number of the experimental cases of this were eventually found to be explained by the phenotypic 'rescue' of I-E chains from En mouse strains by association with complementing chains from the second parent of the F, (Sredni et al, 1981). It is interesting to recall, in the light of the present findings, that one of the cases of Zr gene complementation in the rat, described by Giinther and Rude (1975), involved RTld.…”
Section: Discussionsupporting
confidence: 60%
“…The recent availability of anti-Ia monoclonal antibodies (Hammerling et al, 1979;Ozato et al, 1980;Pierres ef al., 1980) has made possible more detailed serological analyses of Ir gene function (Harris et al, 1980;Hodes et al, 1980;Lerner et al, 1980;Napom et al, 198 1). Although data from inhibition experiments using anti-Ia monoclonal antibodies must be interpreted cautiously (Dubreuil et al, 1982), such experiments have permitted insights into the role of Ia determinants in responses to protein antigens Correspondence: Dr Chella S. David, Department of Immunology, Mayo Clinic and Medical School, Rochester, MN 55905, U.S.A. (Fathman el al., 1981;Srendi et al, 1981). We report here the confirmation of genetic mapping data by serological and functional assays.…”
Section: Introductionsupporting
confidence: 60%
“…It was very surprising that the B 10.A(5R) clone responded better to moth fragment 81-103 with the B10.A Ia molecule than with its own Ia molecule; that is, the B10.A(5R) clone appeared to be heteroclitic for the B10.A restriction element. This is not a general finding for all B10.A(5R) clones because PPD and Gl_4b-specific B10.A(5R) clones cannot be stimulated with antigen in the presence of B 10.A spleen cells (26). It is also not related to the responder status of the donor of the presenting cells because B10.S(gR) (ssskkddd) spleen cells would not present any of the cytochrome c fragments to the B 10.A(5R) clone (see Table I), even though the B 10.S(9R) is a high responder to both moth and pigeon cytochrome c. 3 Thus, the Ia heteroclicity appears to be a specific degeneracy associated with the receptor(s) on moth cytochrome c-reactive B10.A(5R) and B10.A clones.…”
Section: Discussionmentioning
confidence: 92%